Economics and the public interest - Gill, Richard T. (Pacific Palisades, Calif. : Goodyear Pub. Co., 1976)
The book is divided into three parts. Part I. The Modern Economy: Problems, Institutions, and Systems. Part II. The Economy in the Aggregate: National Income, Employment, Inflation, Money, Trade. Part III, Growth, Development, and Future Prospects.
Includes bibliographical references and index.
rpm 10/11/2017
Loans
Keywords: Economics; United States